Analisis Upaya Pemerintah Dalam Pemberdayaan Pedagang Pasar Tanah Abang Pada Tahun 2023-2025 - Muhammad Daffa Alvintra; Neny Marlina (Journal of Politic and Government Studies, 2026)
This study was motivated by the conditions faced by vendors at Tanah Abang Market following the COVID-19 pandemic, including declining trading activities caused by a decrease in visitor numbers, changes in consumer shopping patterns, and the growth of digital commerce. These conditions encouraged the Jakarta Provincial Government, in collaboration with Perumda Pasar Jaya, to implement various empowerment initiatives. This study aims to analyze the government's efforts in empowering vendors at Tanah Abang Market during the 2023-2025 period. The study employs Sumodiningrat's community empowerment theory, which consists of enabling, empowering, and protecting, as well as Mardikanto's theory of empowerment objectives. A qualitative method with a descriptive approach was used through interviews, observations, and documentation. The findings indicate that the government carried out empowerment initiatives through the Jakpreneur Program, digital marketing and e-commerce training, the Yuk Kepasar Program across Jakarta, and facilitation of access to BPJS Ketenagakerjaan. These initiatives reflect the government's efforts to expand business access, strengthen vendors capacities, and support business sustainability in the post-pandemic period. The findings also indicate changes in business conditions, reflected in improved business management knowledge, the growing use of digital technology, improved market conditions, and the maintenance of social relationships among vendors. However, these benefits have not been experienced evenly because participation in empowerment programs remains limited and mentoring has not been conducted sustainably. The study concludes that the government has sought to empower vendors by expanding access, strengthening capacities, and providing support for business sustainability, although program outreach, vendor participation, and the continuity of mentoring remain challenges.